Nutrition management in seniors with malnutrition - Bachratá, Zuzana; Libová, Lubica; Miklovicová, Emília; Debnárová, Jana (Magyar Gerontológia, 2024)
The aim of the study was to find out the incidence rates of risk of malnutrition and malnutrition in seniors living at home and in an elderly care facility, separately for both genders. We also aimed to determine the variability of BMI value in different nutritional statuses of seniors.